Screening and optimization of media components for phytase production of ASUIA 279 in Pichia pastoris system using statistical design - Mahamad Maifiah, Mohd Hafidz; Mohd. Salleh, Hamzah; Jamal, Parveen; Nuge, Tamrin (2011)
The gene encoding for phytase from ASUIA279 has been successfully cloned and expressed in pichia pastoris X-33 under the control of AOX1 promoter, named as HSUIA279(5H)AX. In this study, process and media components were screened for high yield phytase production in small scale culture by using plackett burman design. Three factors identified (Agitation, YNB, Yeast extract) were further optimized by Response Surface methodology (RSM) using Face Centered Composite Design (FCCD). Phytase activity in the optimized media (28 U/ml) increase 64% higher over than it basal media (17.004 U/ml) in the shaken flask culture. The cloning of the phytase enzyme from ASUIA279 into the Pichia pastoris system with minimal and potential media components would be a significant concern for a cost effective measure to produce a high yield and activity enzyme for animal feed application.